Formulation of Hand Sanitizer Gel from Chitosan Shell of Fresh Water Lobster (Cherax Quadricarinatus) - Irvan Andreansyah; Ridwanto Ridwanto (NSMRJ: Nusantara Scientific Medical Research Journal, 2022)
Certain aberrant disorders impair the operation of a portion or the entire body. Infectious diseases can be spread by touching a person's hands or after contact with inanimate objects contaminated with bacteria, which can cause a variety of ailments, including diarrhoea. Using hand sanitizer as the primary deterrent is one of the methods to avoid this transmission. This time, the primary element is a natural substance, such as chitosan. Chitosan can be extracted from the shells of freshwater crayfish and utilized as an antibacterial agent in hand sanitizer formulations. This project intends to produce chitosan from crab shells. Crustacean chitosan can be utilized as an active ingredient in hand sanitizer gel. The production of chitosan begins with the demineralization, deproteination, and deacetylation processes. The resulting chitosan was then used to make hand sanitizer gels with 1, 2, and 3% concentrations. Organoleptic, homogeneity, pH, dispersion, and viscosity tests were then conducted on the gel preparation. The results revealed that the hand sanitizer preparations subjected to organoleptic tests on F1, F2, and F3 did not exhibit any changes in odor, shape, or color; the homogeneity test revealed the absence of coarse grains; the pH obtained on average was within the skin pH range; and the spreadability test revealed that the average was in the range of 5-7 cm, indicating that the formula satisfies the specifications.